(untitled) (Eurasian Research Bulletin, 2021)
The behaviours of an individual wasting organizations time for non-work related activities using internet called cyberloafing. The current conceptual paper attempt to shed the light on factors that had been neglected from the previous literature that could play a role in influencing cyberloafing, by incorporate new theoretical perspective that could help for better understanding the phenomenon. In addition, the current paper trying to explore to what extent psychological factors and individual differences construct can help to explain cyberloafing by incorporating individuals factor to the model such as consideration future consequences which is been neglected in the previous studies. Therefore, the current study expected to have a promising result by incorporate job stress as a meditating between job demands and resources, as well as use CFC as a moderator in the relationship between job stress and cyberloafing. It is expected that extend the JDR model by including construal level theory to explain how individuals responding differently based on their personal future orientation. Thus, this study expected to provide a promising result.